Occurrence of intimal thickening of the peripheral arteries in response to local vibration. Issue 7 (July 1987) - Okada, A; Inaba, R; Furuno, T
Abstract : Experiments were performed to elucidate a possible mechanism for the peripheral circulatory disturbance caused by vibration. Rats were exposed to local vibration (60 Hz, 5 G) on their hind legs for four hours a day for 30 days or 90 days. With exposure for 30 days the small arteries at the exposed site did not change. With exposure for 90 days, however, disruption of the internal elastic lamina was observed in the small arteries. This disruption was followed by focal cell proliferation with regenerative formation of collagen and elastic fibres. The fibrocellular thickening of the intima was further augmented, and in addition a complete stenosis of the lumen of the small arteries was observed. Electron micrography showed that the fibrocellular thickening of the intima consisted of a proliferation of arterial smooth muscle cells and numerous collagen and elastic fibres. These alterations were not observed in the arteries of the controls. The thickness of the media did not differ between the control and exposed groups or in animals with different durations of exposure. Concerning plasma total cholesterol, HDL-cholesterol, and lipoperoxide, there were no significant differences between the control and exposed groups after either 30 or 90 days, but the whole blood viscosity was significantly increased by day 90. This finding may be related to the intimal thickening.